GE_GERICHTE C/16962/2015 vom 26. März 2018 - GE Cour de justice (2018)
BAIL À LOYER ; RÉSILIATION ; BESOIN(EN GÉNÉRAL) ; PRINCIPE DE LA BONNE FOI ; ABUS DE DROIT ; MOTIF ; BAILLEUR(BAIL À LOYER) ; PROLONGATION DU BAIL À LOYER | CO.271; CO.272; CO.272b.al2